Geliat Penulisan Kitab Hadis di Pesantren: Studi Kitab Fadlail Al-Tahajjud wa Qiyam Al-Lail Karya Ahmad Yasin bin Asmuni - Muhtaruddin, M. Bik (LPPM IAIN Kediri, 2018)
It must be acknowledged that hadith study activities in Islamic boarding schools are still less popular when compared to other scientific studies such as Tafsir and Fiqh. Due to this lack of attention to hadith studies, the works of Indonesian scholars in the field of hadith, especially pesantren scholars, are very minimal. Moreover, contemporary scholars, such works are almost non- existent. This article discusses the book Fada>il al-Tahajjud wa Qiyam al-Lail, one of the works born from the Hidayatut Thullab Petuk Islamic boarding school in Kediri Regency. Where several important points are found; first, the book Fadhail al-Tahajjud wa Qiyam al-Lail is a summary of the hadith, athar, and the sayings of scholars about the virtues of Tahajjud prayer narrated by Ibn Abi> Dunya. Second, the quality of the hadith is less considered because the purpose of compiling this book is to motivate the community to be enthusiastic about performing Tahajjud and Qiyam Lail. Third, the book Fada>il al-Tahajjud wa Qiyam al-Lail was born from the needs of the community who wanted a clear basis for evidence, whether from hadith or other sources.